Validity of Teaching Animal Media Booklet (Gastropods) - Rahmayani Rahmayani; Elza Safitri; Abizar Abizar (Journal Of Biology Education Research (JBER), 2024)
Education is an important element for developing knowledge and forming a person's character. The use of varied learning media has been proven to be able to increase student activity in class. Media in the form of booklets is suitable for Gastropod material which tends to require students to memorize. In Gastropod material, there is a lot of material whose application is difficult to find in life and has very broad learning objects. The aim of this research is to test the validity of the Gastropod booklet as an interesting learning resource that suits students' needs. This research uses the Research Development method with the ADDIE development model, but is only carried out to the Develop stage, namely to the validity stage. The results of this research show that the Gastropod booklet learning media is included in the very valid category. It can be concluded that the booklet teaching media is very valid to use for learning science, animalia material, Gastropod sub-material.